Integrated reporting: A new paradigm for corporate reporting - Niaz, Mohammad; Rashedul, Hasan (INTI International University, 2019)
Listed companies are required to publish financial information in their annual reports mandatorily and also publish sustainability and social reports, which comprise their non-financial performance regarding social and environmental issues. To solve this problem would be to create a single report providing a clear link between the financial and nonfinancial issues. In this sense, integrated reporting (IR) has emerged as a new reporting paradigm to provide a more comprehensive view of the entity, rather than the traditional financial report, by combining the financial and non-financial dimensions of the corporate performance. In Bangladesh banks and non-bank financial institutions started to disclose integrated reporting. The study mainly focuses on the integrated reporting disclosure in the financial statement of NBFI (Non-banking financial institutions). The sample for research involved total 20 (twenty) financial institution’s annual report from 2016 to 2017 out of 34. The analysis showed that few financial institutions have taken initiatives to disclose such information voluntarily.